AsTeRICS: a new flexible solution for people with motor disabilities in upper limbs and its implication for rehabilitation procedures. (25th January 2013) - Morales, Blanca; Diaz-Orueta, Unai; García-Soler, Álvaro; Pecyna, Karol; Ossmann, Roland; Nussbaum, Gerhard; Veigl, Christoph; Weiss, Christoph; Acedo, Javier; Soria-Frisch, Aureli
Abstract: Purpose : To present the AsTeRICS construction set, and examine different combinations of sensors installed in the platform and how users interact with them. Method : Nearly 50 participants from Austria, Poland and Spain were included in the study. They had a heterogeneous range of diagnoses, but as a common feature all of them experienced motor limitations in their upper limbs. The study included a 1 h session with each participant where the user interacted with a personalized combination of sensors, based on a previous assessment on their motor capabilities performed by healthcare professionals. The sensors worked as substitutes for a standard QWERTY keyboard and a standard mouse. Semi-structured interviews were conducted to obtain participants' opinions. All collected data were analyzed based on the qualitative methodology. Results : The findings illustrated that AsTeRICS is a flexible platform whose sensors can adapt to different degrees of users' motor capabilities, thus facilitating in most cases the interaction of the participants with a common computer. Conclusion : AsTeRICS platform can improve the interaction between people with mobility limitations and computers. It can provide access to new technologies and become a promising tool that can be integrated in physical rehabilitation programs for people with motor disabilities in their upper limbs. Implications for Rehabilitation: The AsTeRICS platform offers an interesting tool to interface and support the computerized rehabilitation program of the patients. Due to AsTeRICS platform high usability features, family and rehabilitation professionals can learn how to use the AsTeRICS platform quickly fostering the key role of their involvement on patients' rehabilitation. AsTeRICS is a flexible, extendable, adaptable and affordable technology adapted for using computer, environmental control, mobile phone, rehabilitation programs and mechatronic systems. AsTeRICS makes possible an easy reconfiguration and integration of new functionalities, such as biofeedback rehabilitation, without major changes in the system.